Pesan Singkat Film Budi Pekerti: Beretika dalam Bermedia - Rohmah, Muttafaqur (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research discusses the meaning, messages and wisdom displayed by the characters in the film Budi Pekerti. Just like a show, the requirements for meaning and message are also the mandate and wisdom to depict and emulate attitudes, acting and human behavior in life as the meaning and function of a good film. It contains signs that contain many lessons. That's what the film Budi Pekerti wants to convey. Characteristics is not just a film title, but also morals in its plural and real meaning. The morals contained in the nation's values are the values of Pancasila. Good manners in using social media and ethical and wise use of social media. Character films are a long bridge whose end is not yet visible. As if describing the faces of social media and netizens who are always correct with all their posts. In this research, the author dissects the imagination of young filmmakers in Indonesia who not only present love stories, but also social criticism of society. This film is a